Evaluation of a Point-of-Care Device for Hemoglobin and Hematocrit Measurement in Infants Compared with a Standard Laboratory Analyzer - Kadhim , Ali M. (Medical Science Journal for Advance Research, 2026)
Background: Rapid detection of anemia is critical for prompt management in infants. Point-of-care testing (POCT) devices provide immediate results and may be particularly useful in low-resource settings. This study evaluated the Hemochroma PLUS hemoglobinometer for hemoglobin (Hb) and hematocrit (HCT) measurement in infants, compared with the Genex Count 60 laboratory analyzer. Methods: A prospective diagnostic accuracy study was conducted at Al-Zahraa Teaching Hospital for Obstetrics and Pediatrics. Capillary blood samples were collected from 33 infants (age 3–12 months) and analyzed using both Hemochroma PLUS and the reference analyzer. Accuracy, precision, sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated. Bland–Altman analysis and coefficient of variation (CV) were used to assess agreement and precision. Results: Hemochroma PLUS showed good agreement with the reference analyzer for Hb (mean bias 0.75 g/dL, 95% limits of agreement –1.37 to 3.25 g/dL) but overestimated HCT (mean bias 6.1%, 95% LOA –5.69 to 17.9%). Coefficient of variation was similar between devices (Hb CV 0.16–0.18). Sensitivity and specificity for Hb-based anemia detection in infants >6 months were 75% and 100%, respectively, with PPV 100% and NPV 93%. In infants 3–6 months, sensitivity decreased to 25% while specificity remained 100%. Conclusion: Hemochroma PLUS is a rapid, economical, and convenient POCT device suitable for hemoglobin measurement in infants older than six months. While reliable for detecting anemia in older infants, confirmatory laboratory testing is recommended for younger infants, and caution is advised for HCT-based assessments.